Removal of Bisphenol-A using Cyphos IL-101 impregnated Amberlite XAD-7: optimisation using response surface methodology. Issue 14 (14th November 2022) - Batra, Sakshi; Datta, Dipaloy
ABSTRACT: Resins, when impregnated with a solvent shows better stability, higher affinity, and effectiveness in removing pollutants. The interaction of pollutants with the impregnated resin takes place by adsorption, solvent extraction, and ion exchange which enhance the resin capacity. Here, Bisphenol-A (BP-A) was removed from aqueous solution using Cyphos IL-101 impregnated Amberlite XAD-7 resin. FTIR, FE-SEM, TGA, BET, and point of zero charge analysis were used for characterisation. The experiments were designed using CCD of RSM, and an empirical model was developed to optimise input variables. The effective input parameters chosen were: resin dosage ( D : 2 to 4 g/L), initial BP-A concentration ( C : 30 to 50 mg/L), solution pH ( P : 4 to 8), and temperature ( T : 303 to 323 K) and their effect on the responses (percentage removal and adsorption capacity) were studied. At optimum conditions ( D = 5 g/L, C = 58.6 mg/L, P = 8.44, and T = 294.6 K), the experimental and predicted percent removal were found to be 97.56% and 99.99%, respectively. Equilibrium and kinetic data were matched with Freundlich and pseudo-second-order model, respectively. The regenerability study showed good performance of the resin after the 5 th cycle (1 st use: 97.55%, 6 th use: 96.21%).